[Image 33] - Smith, Captain Sir William [?ob. 1732] (My University, 1806)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of Green Castle prior to forming the new works there as seen from [indecipherable] by Sir Wm Smith 1806.
Keywords: Greencastle; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810